Urban myths and the mis-use of data that underpin them - David Satterthwaite (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper describes the gaps and limitations in the data available on urban populations for many low- and middle-income nations and how this limits the accuracy of international comparisons - for instance of levels of urbanization and of the size of city populations. It also discusses how the lack of attention to data limitations has led to many myths and misconceptions in regard to growth rates for city populations and for nations' levels of urbanization. It ends with some comments on how data limitations distort urban policies.
Keywords: O18; C80; F59; 330; urbanization; city populations; censuses